Study of Clinico Radiological Profile of Ischemic Cerebrovascular Stroke and Its Outcome at Tertiary Care Centre (Academia Journal of Medicine, 2020)
Background: Ischemic CV stroke is disease of long term Disability and Death accounts for >80% of total stroke events. The main objective of  the study was to study clinical and radiological profile, risk factors and outcome of stroke. Subjects and Methods: An observational study of  46 patients of acute ischemic cerebrovascular stroke was conducted during January 2014 to November 2014. All patients were subjected to  Sociodemographic, Clinical, family h/o risk factors, dietary, other lifestyle habits and examination with written consent. Apart from routine  blood investigations, special investigations like Uric acid, urinary albumin creatinine ratio, ECG,2D Echo, Carotid Doppler, CT Scan/MRI  brain were done within24 hours of onset. NIHSS and MRS scores were used for severity assessment. Results: Majority of patients were in 55- 64 years (30.4%) age group with male predominance (52%) (mean age 55.52+12.61). Old aged patients are more likely to be selected for  study. Microalbuminuria was found on 34 (73.9%) Patients with recent stroke. 52.1 % patients having serum uric acid >8. 36.9 % patients.  ECG suggested LVH and normal findings in 36.9% while 15.2% and 10.8% had stroke related changes and myocardial ischemia. Majority 30 (65%) of patients showed concentric hypertrophy, followed by diastolic dysfunction 11(23%) on 2D Echo. Atherosclerotic changes seen in  60.8% on carotid Doppler study. majority 32.6 % patients were affected in MCA territory, followed by 23.9 % PCA territory followed by  19.5% infarct in thalamus. NIHSS and MRSmean score was 20.2+ 12 and 3.9+1.8 on admission and 15.7+13 and 3.23+ 1.91 on discharge respectively. Hospital outcome was good. No mortality during entire study period. Conclusion: Stroke a high socioeconomic burden in  community. Apart from Age and hypertension, microalbuminuria and uric acid may be considered as independent risk factors for ischemic  stroke. Identification and treatment of risk factors can prevent stroke related morbidity and mortality.
Keywords: Ischemic cerebrovascular stroke; Atherosclerotic risk factors